THE RELATIONSHIP BETWEEN THERAPEUTIC COMMUNICATION AND THE APPLICATION OF CARING BEHAVIOR FOR NURSING STUDENTS AT STIKES MEDISTRA INDONESIA IN 2023 - Rohayati; I Ratnah; Rotua Suriany Simamora (Rena Cipta Mandiri, 2024)
In therapeutic communication, one must pay attention to the therapeutic communication phase, this communication phase will be formed with a behavior, namely caring behavior. The application of caring behavior needs to be based on the knowledge and application of the therapeutic communication. But in reality nursing students are still found to have poor knowledge of therapeutic communication and caring behavior. The purpose of this study was to determine the relationship between therapeutic communication and the application of caring behavior in students of the Indonesian Medical School Nursing Study Program in 2023. This research method is observational quantitative analytic with a cross-sectional approach and simple random sampling technique and using a questionnaire via Googleform to 65 respondents at STIKes Medistra Indonesia. This study used the chi-square statistical test to determine the relationship between the two variables. Based on the results of the chi square test analysis with Sig. (2-tailed) and a value of 0.050 is obtained by a p value = 0.000 so that it is stated that H0 is rejected Ha is accepted. So that it can be interpreted that there is a relationship between therapeutic communication and the application of caring behavior to nursing students at STIKes Medistra Indonesia in 2023.